2015
DOI: 10.1111/bcp.12814
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment of cardiac glycoside poisoning

Abstract: Cardiac glycosides are an important cause of poisoning, reflecting their widespread clinical usage and presence in natural sources. Poisoning can manifest as varying degrees of toxicity. Predominant clinical features include gastrointestinal signs, bradycardia and heart block. Death occurs from ventricular fibrillation or tachycardia. A wide range of treatments have been used, the more common including activated charcoal, atropine, β-adrenoceptor agonists, temporary pacing, anti-digoxin Fab and magnesium, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 39 publications
(91 reference statements)
0
81
0
1
Order By: Relevance
“…Lesch (Moraceae) [15] and structural analysis with MS and NMR confirmed that ToxH is a cardiac glycoside with a special cardenolide structure ( Figure 1A). Recent studies suggest that cardenolides derive anticancer activities via the induction of cancer apoptosis [16][17][18]. Since ToxH is a new cardenolide structure, its cytotoxicity was confirmed using an MTT assay [15].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lesch (Moraceae) [15] and structural analysis with MS and NMR confirmed that ToxH is a cardiac glycoside with a special cardenolide structure ( Figure 1A). Recent studies suggest that cardenolides derive anticancer activities via the induction of cancer apoptosis [16][17][18]. Since ToxH is a new cardenolide structure, its cytotoxicity was confirmed using an MTT assay [15].…”
Section: Discussionmentioning
confidence: 98%
“…Structural analysis by MS and NMR spectral data and chemical evidence show that ToxH is a cardiac glycoside with a special cardenolide structure ( Figure 1A) [15]. Recent research results indicate that cardenolides extracted from natural sources can have anticancer activity and can block tumor cell proliferation and induce tumor apoptosis via the regulation of several cell signaling pathways and sodium pump inhibition [16][17][18][19], and even through the induction of immunogenic cell death [20][21][22]. At this time, the anticancer activity of cardenolides has not been linked to mitophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Activated charcoal is used to avoid further absorption of the cardiac glycoside and interrupt the enterohepatic circulation. Atropine is preferred for bradycardia or AV blocks and temporal pacing can also be used . The digoxin‐specific antibody fragments are very important in the treatment of moderate or severe intoxication.…”
Section: Drugs With the Major Effects On The Heartmentioning
confidence: 99%
“…Atropine is preferred for bradycardia or AV blocks and temporal pacing can also be used. 305 The digoxin-specific antibody fragments are very important in the treatment of moderate or severe intoxication. As a result of their use, the mortality from digoxin intoxication dropped from 20-30% to 5-8%.…”
Section: F I G U R Ementioning
confidence: 99%
“…Titration to the desired effect is also generally used for atropine (titrated to cholinergic signs in cholinesterase inhibitor poisoning) , flumazenil (coma) , vitamin K (prothrombin time) , protamine (activated partial thromboplastin time), octreotide (blood glucose) , methylene blue (methaemoglobinaemia), calcium (blood pressure) , insulin (blood pressure), physostigmine (coma or delirium) , sodium bicarbonate (blood or urine pH), ethanol (ethanol concentration) and digoxin‐Fab (rate and rhythm) . The dose of an antidote can be far higher than the doses required when these drugs are used for other indications (Table ).…”
Section: Introductionmentioning
confidence: 99%